3 Segmentation of the Paraxial Mesoderm and Vertebrate Somitogenesis - Pourquié, Olivier (Current Topics in Developmental Biology, 1999)
Somites are the most obviously segmented features of the vertebrate embryo. Although the way segmentation is achieved in the fly is now well described, little was known about the molecular mechanisms underlying vertebrate somitogenesis. Through the recent identification of genes important for vertebrate somitogenesis and the analysis of their function, several theoretical models accounting for somitogenesis such as the clock and wavefront model, which have been proposed over the past 20 years, are now starting to receive experimental support. A molecular clock linked to somitogenesis has been identified which might act as a periodicity generator in the presomitic cells. This temporal periodicity is then translated into a tightly controlled spatial periodicity which is revealed by the expression of several genes. Analysis of mouse mutants in the Notch-Delta pathway suggest that this signaling mechanism might play an important role at this level. The final step of the cascade is to translate these genetically specified segments into morphological units: the somites. Importantly, these studies have helped in dissociating the segmentation and the somitogenesis processes in vertebrates. In addition, although segmentation was classically thought to have arisen independently in protostomes and deuterostomes, recent evidence suggests that part of the segmentation machinery might actually have been conserved. The conservation of segmentation mechanisms reported in the fly such as the pair-rule pattern, however, remain a subject of controversy.